Board Game Based Learning HEMBIZIKA - Šljivović, Mladen Milovan (LUMAT-B: International Journal on Math, Science and Technology Education, 2017)
In this paper the concept of the board game Hembizika will be explained. The faults of the first version of HEMBIZIKA will be shortly discussed. The solution led to creation of a new version of the game called HEMBIZIKA 1.2 Rules for HEMBIZIKA 1.2 will be explained and the examples of used questions will be given. The results of implementation in education will be shortly discussed.